Pengaruh Literasi Keuangan Syariah dan Etika Bisnis Islam Terhadap Kinerja Bisnis UMKM di Kabupaten Jepara - musyafa', musyafa' (ITB AAS INDONESIA Surakarta, 2023)
In Indonesia, MSMEs contribute greatly to the economy and directly show their impact. There is a phenomenon regarding business success linked to Islamic financial literacy and Islamic business ethics. This article analyzes and tests the influence of sharia financial literacy and Islamic business ethics on MSME business performance in Jepara Regency. The total population, namely MSMEs, in Jepara Regency is 80,966. Taking samples using the Slovin formula, a sample of 99,876 was obtained or rounded to 100 using the proportional random sampling technique. Data was collected using a questionnaire. Data processing methods use editing, coding, tabulating. Data analysis with multiple linear regression. The partial research results show that sharia financial literacy has a positive and significant effect on MSME business performance with a calculated t of 2.548 & gt; t table 1.66071 is positive and the result is a significant value of 0.012 & lt; 0.05. Islamic business ethics has a positive and significant effect on MSME business performance with a calculated t of 2.560 & gt; t table 1.66071 is positive and the result is a significant value of 0.012 < 0.05.